Donor specific antibodies association with survival and adverse events after heart transplantation: A single center retrospective study between 2006 and 2021. Issue 4 (24th January 2023) - Akhtar, Waqas; Peterzan, Mark A.; Banya, Winston; Olwell, Brian; Aghouee, Farveh Vakilian; Brookes, Paul; Dunning, John; Dar, Owais
Abstract: Objective: Newly detected donor HLA‐specific antibodies (DSA) are historically known to be associated with reduced survival in heart transplant patients. Our objective is to clarify the modern incidence of DSA and determine its relationship with survival and MACE. Methods: This retrospective study included all patients undergoing orthotopic heart transplantation at Harefield Hospital, London between January 1, 2006 and May 31, 2021. We identified patients who developed DSA at any point post heart transplantation and its effect on survival and MACE (defined as rejection, coronary event, stroke, and arrhythmia. Results: In total of 232 patients were included with a median follow up time of 4.7 years post heart transplantation. 23.7% of patients included developed DSA post heart transplantation. There was a significantly increased risk of death in patients developing DSA versus not (sub distribution hazard ratio [SHR] 1.83, 95% confidence interval 1.03–3.24, p  = .04). At the time of detection of DSA, 38.2% of the cohort had rejection necessitating treatment. A MACE event had occurred in 48.1% by 2 years and 53.7% by 3 years in the DSA cohort. There was a significantly increased risk of MACE in patients developing DSA versus not (SHR 2.48 [1.58–3.89, p  < .0001]). Conclusions: This study showed an increased risk of death and MACE in patients developing DSA post heart transplantation. Further research is required into the optimal management of these patients